2019
DOI: 10.3390/nano9081139
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Route to Manufacture 2D Layer MoS2 and g-C3N4 by Atmospheric Plasma with Enhanced Visible-Light-Driven Photocatalysis

Abstract: An atmospheric plasma treatment strategy was developed to prepare two-dimensional (2D) molybdenum disulfide (MoS2) and graphitic carbon nitride (g-C3N4) nanosheets from (NH4)2MoS4 and bulk g-C3N4, respectively. The moderate temperature of plasma is beneficial for exfoliating bulk materials to thinner nanosheets. The thicknesses of as-prepared MoS2 and g-C3N4 nanosheets are 2–3 nm and 1.2 nm, respectively. They exhibited excellent photocatalytic activity on account of the nanosheet structure, larger surface are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Nowadays, a series of post/pre-treatment methods have been proposed to remove the azo dyes from the wastewater [1,[9][10][11]. Porous/activated carbons have been applied as commercial adsorbents for the wastewater treatment thanks to their high capacity for adsorbing pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, a series of post/pre-treatment methods have been proposed to remove the azo dyes from the wastewater [1,[9][10][11]. Porous/activated carbons have been applied as commercial adsorbents for the wastewater treatment thanks to their high capacity for adsorbing pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…One portion was treated by DBD plasma to obtain g-C 3 N 4 /TiO 2 composites according to the procedure reported in previous work [32,33]. Figure S1a shows the DBD device.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in this article, we chose graphitic carbon nitride (g-C 3 N 4 ) to modify BiVO 4 to enhance photocatalytic efficiency due to graphene-like structure, good thermal and chemical stability, good visible light absorption, and photocatalytic properties of g-C 3 N 4 [6]. In addition, g-C 3 N 4 nanosheets could enhance an easier electron transfer during the reaction [9]. Smykalova et al (2019) indicated that g-C 3 N 4 nanosheets possessed a large specific surface area, which resulted in the higher degradation ratio of medicines in water [10].…”
Section: Introductionmentioning
confidence: 99%